Kepemimpinan, Kualitas SDM Dan Kepuasan Kerja Dalam Meningkatkan Kinerja Pegawai Balai Besar Karantina Pertanian Makassar - Haeranah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This research study aims to find out and explain the influence of leadership, human resources quality and job satisfaction in improving employee performance at the Makassar Agricultural Quarantine Center. In this study, Slovin was used in calculating the sample number of 110 employees from a total population of 150 employees. Data analysis methods used quantitative descriptive use multiple linear regression to measure the influence of leadership, HR quality, and job satisfaction in improving employee performance. Based on the F test or simultaneously together leadership, HR quality, and job satisfaction in improving employee performance were able to contribute by 76.0 percent. Leadership is the most dominant factor in improving employee performance in leadership, HR quality, and job satisfaction in improving employee performance at the Makassar Agricultural Quarantine Center.